Elucidating the correlation between the number of TTTTGAT heptamer repeats and cholera toxin promoter activity in Vibrio cholerae O1 pandemic strains. Issue 1 (19th April 2022) - Naha, Arindam; Withey, Jeffrey H; Mukherjee, Piyali; Saha, Rudra Narayan; Samanta, Prosenjit; Ghosh, Amit; Miyoshi, Shin-Ichi; Dutta, Shanta; Mukhopadhyay, Asish K
Abstract: A complex virulence-regulatory cascade controls expression of the cholera toxin genes ( ctxAB ) in Vibrio cholerae, which eventually leads to the production and secretion of choleragen (CT), responsible for rice watery diarrhoea in infected individuals. The cholera toxin promoter (P ctxAB ) contains a series of heptad repeats (5′-TTTTGAT-3′), which has previously been shown to play a crucial role in transcriptional regulation of ctxAB by recruiting the transcriptional activators ToxT, ToxR and the nucleoid-associated protein H-NS along the ctx promoter. The number of these repeats differs not only between the two biotypes of V. cholerae O1 strains, but also among the strains belonging to the same biotype. In this study, we examined if regulation of P ctxAB is influenced in any way by the number of these repeats. Based on our observations, we posit that ctx activation indeed depends on the number of TTTTGAT heptad repeats within P ctxAB, and occupation of the distal repeats by H-NS could prevent transcriptional activation of the ctx genes in V. cholerae O1 pandemic isolates. Our results suggest that ToxT-dependent transcriptional activation may not require entire displacement of H-NS and supports a recently described revised model of ToxT and H-NS mediated P ctxAB transcriptional regulation. Abstract : Regulation of cholera toxin operon promoter activity by distal repeats supports a recently described model of virulence regulation by the repressor protein H-NS and master virulence regulator ToxT.